Antiretroviral drugs: predicted environmental concentration and ecological risk Assessment in Sewage Treatment Plants in Cubatão, São Paulo, Brazil (Research, Society and Development, 2022)
Predictive models have been used worldwide as an important approach to investigate the presence of drugs in aquatic ecosystems, mainly due to the disposal of effluents generated by Sewage Treatment Plants (STP). The objective of this study was to estimate the environmental concentrations and potential ecological risks of fourteen antiretroviral drugs (ADs), which are released in the aquatic ecosystems of Cubatão, through two STPs. The Predicted Environmental Concentration (PEC) was calculated according to the guidelines of the European Medicines Agency (EMEA) and the Ecological Risk Assessment (ERA) was predicted considering three trophic levels: algae, crustaceans and fish. The results indicated that the fourteen ADs (PEC ranges between 0.05 and 20.29 µg/L) exceeded the ecological safety limits established by the EMEA guideline (PEC > 0.01 µg/L). After performing the ERA, the results showed the following trend: (i) 71.43% of the assessments indicated high acute risk for the three trophic levels tested. Regarding chronic toxicity, 57.14% of the evaluations also indicated high risks. Based on the results a prioritization list of the most toxic ADs was created. The final ranking of the most toxic ADs was established as follows: 1st place, Lopinavir and Ritonavir (top priority); Maraviroc (2nd place); Efavirenz, Darunavir, Dolutegravir and Zidovudine (3rd place); Atazanavir, Etravirine and Nevirapine (4th place); Abacavir, Raltegravir and Tenofovir (5th place) and, finally, Lamivudine, which indicated the least environmental concern. The data obtained may provide subsidies for the planning of actions aimed at improving the quality of coastal and marine ecosystems in the country.